Exploring the prospects for adaptive governance in marine transboundar y conservation in East Africa - Tuda, Arthur Omondi; Kark, Salit; Newton, Alice (Marine Policy, 2019)
This article explores the prospects for adaptive governance in a propo sed marine transboundary conservation initiative in East Africa. Adapt ive governance that involves interdependent state and non-state actors learning and taking action on joint environmental problems is suggest ed for effective transboundary resource governance. Using the concept of adaptive co-management, the current multi-stakeholder marine govern ance systems in southern Kenya and northern Tanzania are compared to i lluminate opportunities and constraints for adaptive marine transbound ary conservation governance between Kenya and Tanzania. The concept of networks and the formal method of social network analysis (SNA) are a pplied as the main methodological device. Using questionnaire and semi -structured interviews, social network data of 70 organizations (local resources users, government agencies and NGOs) was generated from Ken ya (n = 33) and Tanzania (n = 37). Results show the existence of stron g collaboration networks for marine resource governance in both Kenya and Tanzania. Social proximity is the common driver of network formati on. Collaboration networks in Kenya and Tanzania have contributed to e nhanced learning among marine resource managers. Conclusions point to the need to focus on common challenges relating to low levels of rule- compliance, limited access to information on the state of resources an d poor integration of science into marine management decisions. Finall y, differences in views regarding the state of marine ecosystems need to be addressed to improve prospects for joint problem-solving in mari ne transboundary conservation.
Keywords: Adaptive co-management; Adaptive governance; Collaboration; Marine transboundary conservation; Social network analysis